Pengaruh self-efficacy matematis terhadap kemampuan penalaran matematis siswa dalam situasi online learning - Farah Heniati Santosa; Samsul Bahri (Journal of Didactic Mathematics, 2022)
The purpose of the study was to determine the effect of mathematical self-efficacy on mathematical reasoning abilities in online learning situations. The research design is quantitative descriptive on 75 students of class XI SMA Negeri in one of Mataram City State. The data collection is in the form of a mathematical reasoning ability test score consisting of 5 items, and a 20-point SEM questionnaire. Data analysis using simple regression. The results showed that there was a significant positive relationship between mathematical self-efficacy and students' mathematical reasoning abilities. The simple regression equation, namely: Y = 38.075 + 0.483X explains how students' mathematical reasoning abilities can be improved by increasing mathematical self-efficacy. Observation of other factors in the formulation of the regression equation is important for further research, considering that the results of these findings show that the correlation between mathematical self-efficacy and mathematical reasoning ability is only 14.8%.